(3TQM eYGfi cJGH GdbGfhf aj GdWH dGHf SjfGs - (3YdGA GdOjf Ydj Hf CHi GdMRe GdbQTi ,GHf GdfajSs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd Gdehdi GdGSJGP GdLdjd GdYGde GdYGed YdGA GdOjf CHf CHj GdMRe GdbQTi bUOfG HgPG GdcJGH Cf fTQM eYGfi cJGH GdbGfhf ddTjN GdQFjS Edi Ydi Hf SjfG bOS Gddg QhMg TQMkG jLY Edi GdEjLGR GdEjVGM s
(3BNQgG (B:s
(3bGd GdTjN GdQFjS hCeG GdOGaYI aEfgG JOaY TQM (B: (3bO MUQfG GdaVdGJ GdHOfjI s
(3HGdhQbI GdCNjQI BKGQ cTW ef GdcJGHg ai hSW GdSWhQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdWH (B- - (3U (B111 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B136 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B270 s
Keywords: (3GdWHs